α-spinasterol isolated from Achyranthes aspera L. ameliorates inflammation via NF-κB and Nrf2/HO-1 pathways - Qiongli Zeng; Weiting Xiao; Heng Zhang; Wei Liu; Xionglong Wang; Zhen Li; Yue Han; Zhi Wang; Shunxiang Li; Jinwei Yang; Wen Ouyang (Scientific Reports)
Abstract On the basis of previous studies, the low-polar part of Achyranthes aspera L. (A. aspera) had strong anti-inflammatory activity. Three compounds were isolated from the low polarity fraction of A. aspera, and their structures were identified as α-spinasterol (1), 7,8-dihydrospinasterol (2), 22,23-dihydrospinasterol (3). Among them, the content of α-spinasterol (1) in A. aspera was higher in the spring and winter seasons through HPLC methods, ranging from 0.0085 to 0.0157%. Futhermore, in the LPS-induced RAW264.7 cells inflammation model, α-spinasterol significantly reduced the levels of cytokines such as IL-6, PGE2 and TNF-α, inhibited the expression of COX-2, 5-LOX, p-IKKβ, p-NFκB and p-IkBα proteins, and promoted the expression of Nrf2, HO-1 and NQO1 proteins. Therefore, this study showed that α-spinasterol can inhibit LPS-induced RAW264.7 cells inflammation, and its mechanism may be related to the inhibition of NF-κB pathway, activation of Nrf2 pathway, and reduction of excessive release of inflammatory factors.